Automobile industry of China: past, present and future. (24th February 2006) - Lee, Hyun-Sook; Anderson, Beverlee B.
China is poised to become a major player in world markets in a variety of industries. The government has recently designated the automobile industry as one of the pillars for its economic growth and development. This paper examines the auto industry as it has developed and its potential within the framework of Porter's Diamond Model.